2017
DOI: 10.1096/fj.201601359rr
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of epidermal growth factor receptor in renal proximal tubule induces tubulointerstitial fibrosis

Abstract: Epidermal growth factor receptor (EGFR) has been implicated in the pathogenesis of diabetic nephropathy and renal fibrosis; however, the causative role of sustained EGFR activation is unclear. Here, we generated a novel kidney fibrotic mouse model of persistent EGFR activation by selectively expressing the EGFR ligand, human heparin-binding EGF-like growth factor (hHB-EGF), in renal proximal tubule epithelium. hHB-EGF expression increased tyrosine kinase phosphorylation of EGFR and the subsequent activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 45 publications
(81 reference statements)
5
55
0
Order By: Relevance
“…In the hHB-EGF Tg/Tg model, renal tubulointerstitial fibrosis develops by 6 weeks of age and its level increases longitudinally as the mouse ages. 6 The hHB-EGF Tg/Tg mice at 16 weeks showed evident increments in tPSR-detected regions compared with normal WT mice ( Figure 5). The sensitivity and specificity of tPSR were the highest to fibrosis among the MRI parameters in this study ( Figure 6 and Table 3).…”
Section: Sensitivity Of Mt Measures To Renal Tubulointerstitial Fibmentioning
confidence: 93%
See 2 more Smart Citations
“…In the hHB-EGF Tg/Tg model, renal tubulointerstitial fibrosis develops by 6 weeks of age and its level increases longitudinally as the mouse ages. 6 The hHB-EGF Tg/Tg mice at 16 weeks showed evident increments in tPSR-detected regions compared with normal WT mice ( Figure 5). The sensitivity and specificity of tPSR were the highest to fibrosis among the MRI parameters in this study ( Figure 6 and Table 3).…”
Section: Sensitivity Of Mt Measures To Renal Tubulointerstitial Fibmentioning
confidence: 93%
“…In hHB-EGF Tg/Tg mice, the contrasts in some derived parametric maps were unlike those observed in normal WT mice ( Figure 2), consistent with the associated pathologic changes. 6 The characteristic PSR map of hHB-EGF Tg/Tg kidney shows scattered clusters of abnormally high PSR values (indicated by the arrow in Figure 2B) located in the OSOM (the conjunction between cortex and ISOM). The MTR maps were also compared between WT and hHB-EGF Tg/Tg kidneys, but they were not significantly different ( Figure 2).…”
Section: Mri Characteristics Of Normal Wt and Fibrotic Hhb-egf Tg/tmentioning
confidence: 98%
See 1 more Smart Citation
“…CCN2 has been shown to be involved in several proliferative disorders [5][6][7][8][9][10]. Several EGFR ligands, such as epidermal growth factor (EGF), heparin-binding EGF, epiregulin, and CCN2, can induce proliferation, migration and invasion of epithelial cells and fibroblasts [44,[56][57][58][59]. Now, we have found that CCN2, via EGFR signalling activation, can regulate cell proliferation in the kidney, as demonstrated by the increased number of PCNA-positive proliferating cells.…”
Section: Evaluation Of Potential Mechanisms Involved In Ccn2(iv)-indumentioning
confidence: 99%
“…TGF-β1 binds to type II receptors, which then recruits and activates type I receptors to shape a heteromeric TGF-β1 receptor complex. 23,24 Antisense oligodeoxynucleotide (ODN) containing the target mRNA sequence has been developed as a promising strategy to modulate targeted gene deletion through hybridization with Mrna. The phosphorylated Smad2/3 combines with Smad4, and this complex translocates to the nucleus and controls fibrotic gene expression.…”
Section: Introductionmentioning
confidence: 99%